FAKTOR KEBERHASILAN IMPLEMENTASI PROGRAM LITERASI MEDIA DIGITAL DI KALANGAN MAHASISWA DKI JAKARTA - Tavida Priskila; , Amni Zakarsyi Rahman; Retna Hanani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
Students as agents of the nation should be able to use digital media to increase the productivity of economic, social, and political life. In reality, students are still involved in negative content. With Digital Media Literacy, the government hopes that students will be able to be smart in media. In the realization of Digital Media Literacy, the organizers replaced the pre-test and post-test stages with quizzes whose systems were answered voluntarily. This research uses descriptive qualitative methods. This research found that most of the implementation of Digital Media Literacy was successfully carried out according to the technical guidelines of implementation.The internal driving factors in the implementation of the program consist of the interests affected, the position of the formulator, the implementor of the program and the support of resources. While, the external driving factor lies in the implementation stage, which consists of ; power, interests, and actor strategy; characteristics of the institution; and compliance and responsiveness. An internally inhibiting factor in the implementation of the program in the preparatory stage is the desired degree of change. Meanwhile, the external inhibiting factor in the post-implementation stage of the Digital Media Literacy Program is the type of benefit generated post-implementation. The conclusion of this study is that the implementation of the Digital Media Literacy Program among DKI Jakarta students has generally been successfully implemented, driven by internal and external factors. The suggestion in this study is that the implementing party needs to carry out a post-test seriously to find out the impact of the implementation of the activity.